Penerapan Teknologi Sentrifugasi dalam Pembuatan Virgin Coconut Oil (VCO) di Desa Bojong, Panjatan, Kulon Progo - Anna Pudianti; Boy Rahardjo Sidharta; Yohana Rustiana; Yitno Purwoko; Kenjikoh Kuputra; Jeremiah Tamba (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Bojong Village has a vast coconut plantation potential, which has been planned for utilization and preservation, particularly as a tourist attraction. Coconuts, with their benefits from the roots to the leaves, have long been protected and developed by the local community, including as a producer of Virgin Coconut Oil (VCO). The Bojong village community has been producing VCO using a traditional